Anti-Candida activity of terpenes from Salvia ovalifolia, S. procurrens and S. uliginosa, native to South Brazil - Cristiano da Silva Sousa; Letícia Mezzomo; Juliana Caroline Butzge; Gabriela de Carvalho Meirelles; Sérgio Augusto de Loreto Bordignon; Gilsane Lino von Poser; Miriam Apel (Drug Analytical Research, 2023)
The essential oils of Salvia ovalifolia, S. procurrens and S. uliginosa were obtained by hydrodistillation and analyzed by gas chromatography-mass spectrometry. The three species displayed very low amounts of essential oils, consisting of a few sesquiterpenes, and aliphatic compounds such as aldehydes and long-chain fatty acids. From the leaves of S. uliginosa, an exudate was obtained which presented the diterpene icetexone as the major component. The exudate and icetexone were evaluated for the activity against Candida species, both showing inhibition of fungal growth.